Proceedings of the Third BlackboxNLP Workshop on Analyzing and Interpreting Neural Networks for NLP 2020
DOI: 10.18653/v1/2020.blackboxnlp-1.23
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the Compositional Structure of Vector Representations with Role Learning Networks

Abstract: How can neural networks perform so well on compositional tasks even though they lack explicit compositional representations? We use a novel analysis technique called ROLE to show that recurrent neural networks perform well on such tasks by converging to solutions which implicitly represent symbolic structure. This method uncovers a symbolic structure which, when properly embedded in vector space, closely approximates the encodings of a standard seq2seq network trained to perform the compositional SCAN task. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…We excluded grounded data sets such as CLEVR (Johnson et al, 2017) and SQOOP (Bahdanau et al, 2018), which contain more than one modality. Furthermore, we did not include studies whose primary focus is on how neural networks implement compositional structures (Giulianelli, Harding, Mohnert, Hupkes, & Zuidema, 2018;Lakretz et al, 2019;McCoy, Linzen, Dunbar, & Smolensky, 2019;Soulos, McCoy, Linzen, & Smolensky, 2019;Weiss, Goldberg, & Yahav, 2018a) or studies that evaluate compositionality only based on models' representations (Andreas, 2019). 3.…”
Section: Arithmetic Language and Mathematical Reasoningmentioning
confidence: 99%
“…We excluded grounded data sets such as CLEVR (Johnson et al, 2017) and SQOOP (Bahdanau et al, 2018), which contain more than one modality. Furthermore, we did not include studies whose primary focus is on how neural networks implement compositional structures (Giulianelli, Harding, Mohnert, Hupkes, & Zuidema, 2018;Lakretz et al, 2019;McCoy, Linzen, Dunbar, & Smolensky, 2019;Soulos, McCoy, Linzen, & Smolensky, 2019;Weiss, Goldberg, & Yahav, 2018a) or studies that evaluate compositionality only based on models' representations (Andreas, 2019). 3.…”
Section: Arithmetic Language and Mathematical Reasoningmentioning
confidence: 99%
“…Further work has found impressive degrees of syntactic structure in Transformer encodings (Hewitt and Manning, 2019) (Soulos et al, 2020) Our position in this paper is simple: we argue that the literature on syntactic probing is methodologically flawed, owing to a conflation of syntax with semantics. We contend that no existing probing work has rigorously tested whether BERT encodes syntax, and a fortiori this literature should not be used to support this claim.…”
mentioning
confidence: 83%
“…Implicit TPR Encodings in Neural Networks showed that, in GRUbased (Cho et al, 2014) encoder-decoder networks performing fully-compositional string manipulations, trained on extensive data that fully exemplifies the range of possible compositions, the medial encoding between encoder and decoder could be extremely well approximated by TPRs. Soulos et al (2019) presented the ROLE model that learns its own role scheme to optimize the fit of a TPR approximation to a given set of internal representations in a pre-trained target neural network, removing the need for human-generated hypotheses about the role schemes the network might be implementing. While this work successfully interprets the Tensor Product Representation in fully compositional tasks, abstractive summarization, as well as most other NLP tasks, are only partially compositional and the symbolic rules in language are much more complex.…”
Section: Related Workmentioning
confidence: 99%